Brief psychotic disorder related to areca nut use: a case report - Li, Sixun; Li, Zhixiong; Chen, Juan; Wang, Feng; Ou, Ying; Huang, Yi; Li, Zhe (Frontiers in Psychiatry, 2024)
Background Areca Nut (AN) is the fourth most commonly abused drug after nicotine, ethanol, and caffeine, due to its psychoactive properties provided by bioactive substances. Although previous studies have demonstrated AN’s anxiolytic-like activity and potential benefits in ameliorating symptoms of depression and schizophrenia, there remains limited awareness regarding its association with brief psychotic disorder. Case presentation This case report presents the clinical profile of a 30-year-old male patient with a history of betel nut chewing for the past 2 years, who exhibited sudden onset delusions, hallucinations, and disorganized speech and behavior upon increasing the dosage of betel nut consumption. The patient displayed a positive response to antipsychotic treatment, and symptoms resolved upon discontinuation of betel nut consumption. However, one month after discharge, the patient experienced a recurrence of auditory hallucinations upon resuming betel nut chewing. Through counseling and support, the importance of abstaining from betel nut use and maintaining medication compliance was emphasized, resulting in no recurrence of psychotic symptoms during the six-month follow-up. Conclusions This case report highlights the related role of betel nut with brief psychotic disorder, especially when the chewing dosage is abruptly increased. It underscores the importance of considering betel nut as a potential precipitant related to acute psychiatric disorders in clinical settings.